Bilingualism and Creativity: Towards a Situated Cognition Approach. (24th March 2018) - van Dijk, Marloes; Kroesbergen, Evelyn H.; Blom, Elma; Leseman, Paul P. M.
Abstract: In this paper, the association between bilingualism and creativity is investigated. In the first part, the results of a literature review are reported. Previous research predominantly found that bilinguals outperform monolinguals on creativity tasks, which was explained by bilinguals' enhanced executive functioning compared to monolinguals, and their experience with multiple cultures. Most previous research has examined the relationship between bilingualism and creativity within a psychological trait framework, which does not take into account that cognitive processes are regarded to be situated‐embodied, meaning that they are influenced by environmental factors, and by a person's perceptions of and actions towards these environmental factors. In the second part, we discuss an alternative approach, in which creativity can be defined as the emerging skill of an individual to discover affordances, to come up with creative ideas and products. Recommendations for future research are discussed as well.